Ingenol mebutate: a novel treatment for actinic keratosis. (May 2014) - Collier, Nicholas J; Ali, Faisal R; Lear, John T
A novel, topically applied, short course therapy for actinic keratoses (AK) is now widely licensed following first approval in the USA in 2012. The active agent, ingenol mebutate, is a naturally occurring diterpenoid found in the plant Euphorbia peplus . AK, the most common premalignant dermatological pathology, is increasing in prevalence with increased UV radiation exposure and aging populations, and has the potential to progress to malignant disease. Various treatment modalities exist for AK and the choice for the clinician and patient is now extended with this novel treatment, which requires topical application for only 2 or 3 days, and has cosmetic and tissue-sparing advantages. Ingenol mebutate gel is used as a field-directed therapy, thereby potentially reducing perilesional subclinical AK.